Volume 8 (2007), Issue 4, Article 95, 10 pp. COEFFICIENT INEQUALITIES FOR CERTAIN CLASSES OF ANALYTIC AND UNIVALENT FUNCTIONS TOSHIO HAYAMI, SHIGEYOSHI OWA, AND H.M. SRIVASTAVA D EPARTMENT OF M ATHEMATICS K INKI U NIVERSITY H IGASHI -O SAKA , O SAKA 577-8502 JAPAN ha_ya_to112@hotmail.com D EPARTMENT OF M ATHEMATICS K INKI U NIVERSITY H IGASHI -O SAKA , O SAKA 577-8502 JAPAN owa@math.kindai.ac.jp D EPARTMENT OF M ATHEMATICS AND S TATISTICS U NIVERSITY OF V ICTORIA V ICTORIA , B RITISH C OLUMBIA V8W 3P4 C ANADA harimsri@math.uvic.ca Received 09 August, 2007; accepted 12 September, 2007 Communicated by Th.M. Rassias A BSTRACT. For functions f (z) which are starlike of order α, convex of order α, and λ-spirallike of order α in the open unit disk U, some interesting sufficient conditions involving coefficient inequalities for f (z) are discussed. Several (known or new) special cases and consequences of these coefficient inequalities are also considered. Key words and phrases: Coefficient inequalities, Analytic functions, Univalent functions, Spiral-like functions, Starlike functions, Convex functions. 2000 Mathematics Subject Classification. Primary 30A10, 30C45; Secondary 26D07. 1. I NTRODUCTION , D EFINITIONS AND P RELIMINARIES Let A0 be the class of functions f (z) of the form: (1.1) f (z) = a0 + a1 z + ∞ X an z n , n=2 The present investigation was supported, in part, by the Natural Sciences and Engineering Research Council of Canada under Grant OGP0007353. 260-07 2 T OSHIO H AYAMI , S HIGEYOSHI OWA , AND H.M. S RIVASTAVA which are analytic in the open unit disk U = {z : z ∈ C and |z| < 1} . If f (z) ∈ A0 is given by (1.1), together with the following normalization: a0 = 0 and a1 = 1, then we say that f (z) ∈ A. If f (z) ∈ A satisfies the following inequality: 0 zf (z) >α (z ∈ U; 0 5 α < 1), (1.2) R f (z) then f (z) is said to be starlike of order α in U. We denote by S ∗ (α) the subclass of A consisting of functions f (z) which are starlike of order α in U. Similarly, we say that f (z) is in the class K(α) of convex functions of order α in U if f (z) ∈ A satisfies the following inequality: zf 00 (z) (1.3) R 1+ 0 >α (z ∈ U; 0 5 α < 1). f (z) It is easily observed from (1.2) and (1.3) that (see, for details, [3]) f (z) ∈ K(α) ⇐⇒ zf 0 (z) ∈ S ∗ (α) (0 5 α < 1). As usual, in our present investigation, we write S ∗ := S ∗ (0) and K := K(0). Furthermore, we let B denote the class of functions p(z) of the form: ∞ X p(z) = 1 + pn z n , n=1 which are analytic in U. Each of the following lemmas will be needed in our present investigation. Lemma 1. A function p(z) ∈ B satisfies the following condition: R[p(z)] > 0 (z ∈ U) if and only if p(z) 6= ζ −1 ζ +1 (z ∈ U; ζ ∈ C; |ζ| = 1). Proof. For the sake of completeness, we choose to give a proof of Lemma 1, even though it is fairly obvious that the following bilinear (or Möbius) transformation: z−1 w= z+1 maps the unit circle ∂U onto the imaginary axis R(w) = 0. Indeed, for all ζ such that |ζ| = 1 (ζ ∈ C), we set ζ −1 w= (ζ ∈ C; |ζ| = 1). ζ +1 Then 1 + w = 1, |ζ| = 1 − w which shows that ζ −1 R(w) = R =0 (ζ ∈ C; |ζ| = 1). ζ +1 J. Inequal. Pure and Appl. Math., 8(4) (2007), Art. 95, 10 pp. http://jipam.vu.edu.au/ C OEFFICIENT I NEQUALITIES FOR C ERTAIN C LASSES OF A NALYTIC AND U NIVALENT F UNCTIONS Moreover, by noting that p(0) = 1 for p(z) ∈ B, we know that ζ −1 p(z) 6= (z ∈ U; ζ ∈ C; |ζ| = 1). ζ +1 This evidently completes the proof of Lemma 1. 3 ∗ Lemma 2. A function f (z) ∈ A is in the class S (α) if and only if ∞ X (1.4) 1+ An z n−1 6= 0, n=2 where n + 1 − 2α + (n − 1)ζ an . 2 − 2α An = Proof. Upon setting zf 0 (z) f (z) p(z) = −α f (z) ∈ S ∗ (α) , 1−α we find that p(z) ∈ B Using Lemma 1, we have zf 0 (z) f (z) (1.5) −α 1−α (z ∈ U). and R[p(z)] > 0 6= ζ −1 ζ +1 (z ∈ U; ζ ∈ C; |ζ| = 1), which readily yields (ζ + 1)zf 0 (z) + (1 − 2α − ζ)f (z) 6= 0 f (z) ∈ S ∗ (α); z ∈ U; ζ ∈ C; |ζ| = 1 . Thus we find that (ζ + 1)z + (ζ + 1) ∞ X ! nan z n + (1 − 2α − ζ) z + n=2 ∞ X ! an z n 6= 0 n=2 (z ∈ U; ζ ∈ C; |ζ| = 1), that is, that (1.6) 2(1 − α)z 1+ ∞ X n + 1 − 2α + (n − 1)ζ n=2 2(1 − α) ! an z n−1 6= 0 (z ∈ U; ζ ∈ C; |ζ| = 1). Now, dividing both sides of (1.6) by 2(1 − α)z (z 6= 0), we obtain ∞ X n + 1 − 2α + (n − 1)ζ 1+ an z n−1 6= 0 2(1 − α) n=2 (z ∈ U; ζ ∈ C; |ζ| = 1), which completes the proof of Lemma 2 (see also Remark 2 below). Remark 1. It follows from the normalization conditions: a0 = 0 and a1 = 1 that A0 = 1 − 2α − x a0 = 0 and 2 − 2α J. Inequal. Pure and Appl. Math., 8(4) (2007), Art. 95, 10 pp. A1 = 2 − 2α a1 = 1. 2 − 2α http://jipam.vu.edu.au/ 4 T OSHIO H AYAMI , S HIGEYOSHI OWA , AND H.M. S RIVASTAVA Remark 2. The assertion (1.4) of Lemma 2 is equivalent to ! 2 z + ζ+2α−1 z 1 2−2α f (z) ∗ 6= 0 (z ∈ U), z (1 − z)2 which was given earlier by Silverman et al. [2]. Furthermore, in its special case when α = 0, Lemma 2 yields a recent result of Nezhmetdinov and Ponnusamy [1] for the sufficient conditions involving the coefficients of f (z) to be in the class S ∗ . The object of the present paper is to give some generalizations of the aforementioned result due to Nezhmetdinov and Ponnusamy [1]. We also briefly discuss several interesting corollaries and consequences of our main results. 2. C OEFFICIENT C ONDITIONS FOR F UNCTIONS IN THE C LASS S ∗ (α) Our first result for functions f (z) to be in the class S ∗ (α) is contained in Theorem 1 below. Theorem 1. If f (z) ∈ A satisfies the following condition: n " k # ∞ X X X β γ (−1)k−j (j + 1 − 2α) aj k−j n−k n=2 k=1 j=1 " k # ! ∞ X X β γ + (−1)k−j (j − 1) aj (2.1) 5 2(1 − α) k − j n − k k=1 j=1 (0 5 α < 1; β ∈ R; γ ∈ R), then f (z) ∈ S ∗ (α). Proof. First of all, we note that (1 − z)β 6= 0 and (1 + z)γ 6= 0 (z ∈ U; β ∈ R; γ ∈ R). Hence, if the following inequality: ! ∞ X (2.2) 1+ An z n−1 (1 − z)β (1 + z)γ 6= 0 (z ∈ U; β ∈ R; γ ∈ R) n=2 holds true, then we have 1+ ∞ X An z n−1 6= 0, n=2 which is the relation (1.4) of Lemma 2. It is easily seen that (2.1) is equivalent to ! ∞ ! ∞ ! ∞ X X X n−1 n n n (2.3) 1+ 6= 0, An z (−1) bn z cn z n=2 n=0 n=0 where, for convenience, β γ bn := and cn := . n n Considering the Cauchy product of the first two factors, (2.3) can be rewritten as follows: ! ∞ ! ∞ X X (2.4) 1+ Bn z n−1 cn z n 6= 0, n=2 J. Inequal. Pure and Appl. Math., 8(4) (2007), Art. 95, 10 pp. n=0 http://jipam.vu.edu.au/ C OEFFICIENT I NEQUALITIES FOR C ERTAIN C LASSES OF A NALYTIC AND U NIVALENT F UNCTIONS where Bn := n X 5 (−1)n−j Aj bn−j . j=1 Furthermore, by applying the same method for the Cauchy product in (2.4), we find that ! ∞ n X X Bk cn−k z n−1 6= 0 1+ (z ∈ U) n=2 k=1 or, equivalently, that 1+ " n ∞ k X X X n=2 k=1 ! (−1)k−j Aj bk−j # cn−k z n−1 6= 0 (z ∈ U). j=1 Thus, if f (z) ∈ A satisfies the following inequality: ! ∞ X n k X X (−1)k−j Aj bk−j cn−k 5 1, n=2 k=1 j=1 that is, if ! ∞ X n k X X 1 (−1)k−j [(j + 1 − 2α) + (j − 1)ζ]aj bk−j cn−k 2(1 − α) n=2 k=1 j=1 " k # ∞ n X X X 1 k−j 5 (−1) (j + 1 − 2α)aj bk−j cn−k 2(1 − α) n=2 k=1 j=1 n " k ! # X X +|ζ| (−1)k−j (j − 1)bk−j aj cn−k k=1 51 j=1 (0 5 α < 1; ζ ∈ C; |ζ| = 1), then f (z) ∈ S ∗ (α). This completes the proof of Theorem 1. Setting α = 0 in Theorem 1, we deduce the following corollary. Corollary 1. If f (z) ∈ A satisfies the following condition: n " k # ∞ X X X β γ (−1)k−j (j + 1) aj k−j n−k n=2 k=1 j=1 " k # ! ∞ X X β γ (2.5) + (−1)k−j (j − 1) aj 52 k−j n−k k=1 j=1 (β ∈ R; γ ∈ R), then f (z) ∈ S ∗ . Remark 3. If, in the hypothesis (2.5) of Corollary 1, we set β − 1 = γ = 0 or β = γ = 1 or β − 2 = γ = 0, we arrive at the result given by Nezhmetdinov and Ponnusamy [1]. Moreover, for β = γ = 0 in Theorem 1, we obtain Corollary 2 below. J. Inequal. Pure and Appl. Math., 8(4) (2007), Art. 95, 10 pp. http://jipam.vu.edu.au/ 6 T OSHIO H AYAMI , S HIGEYOSHI OWA , AND H.M. S RIVASTAVA Corollary 2. If f (z) ∈ A satisfies the following coefficient inequality: ∞ X (2.6) (n − α)|an | 5 1 − α (0 5 α < 1), n=2 then f (z) ∈ S ∗ (α). In particular, by putting α = 0 in (2.6), we get the following well-known coefficient condition for the familiar class S ∗ of starlike functions in U. Corollary 3. If f (z) ∈ A satisfies the following coefficient inequality: ∞ X (2.7) n|an | 5 1, n=2 ∗ then f (z) ∈ S . We next derive the coefficient condition for functions f (z) to be in the class K(α). Theorem 2. If f (z) ∈ A satisfies the following condition: " k # ∞ n X X X β γ (−1)k−j j(j + 1 − 2α) aj k−j n−k n=2 k=1 j=1 ∞ " k # ! X X β γ (2.8) + (−1)k−j j(j − 1) aj 5 2(1 − α) k−j n−k k=1 j=1 (0 5 α < 1; β ∈ R; γ ∈ R), then f (z) ∈ K(α). Proof. Since zf 0 (z) belongs to the class S ∗ (α) if and only if f (z) is in the class K(α), and since f (z) = z + (2.9) ∞ X an z n n=2 and zf 0 (z) = z + (2.10) ∞ X nan z n , n=2 upon replacing aj in Theorem 1 by jaj , we readily prove Theorem 2. By considering some special values for the parameters α, β and γ, we can deduce the following corollaries. Corollary 4. If f (z) ∈ A satisfies the following condition: " k # ∞ n X X X β γ (2.11) (−1)k−j j(j + 1)(−1)k−j aj k − j n − k n=2 k=1 j=1 ∞ " k # ! X X β γ + (−1)k−j j(j − 1) aj 5 2 (β ∈ R; γ ∈ R), k−j n−k k=1 j=1 then f (z) ∈ K. J. Inequal. Pure and Appl. Math., 8(4) (2007), Art. 95, 10 pp. http://jipam.vu.edu.au/ C OEFFICIENT I NEQUALITIES FOR C ERTAIN C LASSES OF A NALYTIC AND U NIVALENT F UNCTIONS 7 Corollary 5. If f (z) ∈ A satisfies the following coefficient inequality: ∞ X (2.12) n(n − α)|an | 5 1 − α (0 5 α < 1), n=2 then f (z) ∈ K(α). Corollary 6. If f (z) ∈ A satisfies the following coefficient inequality: ∞ X (2.13) n2 |an | 5 1, n=2 then f (z) ∈ K. 3. C OEFFICIENT C ONDITIONS FOR F UNCTIONS IN THE C LASS SP(λ, α) In this section, we consider the subclass SP(λ, α) of A, which consists of functions f (z) ∈ A if and only if the following inequality holds true: 0 zf (z) π π iλ (3.1) R e −α >0 z ∈ U; 0 5 α < 1; − < λ < . f (z) 2 2 For f (z) ∈ SP(λ, α), we first derive Lemma 3 below. Lemma 3. A function f (z) ∈ A is in the class SP(λ, α) if and only if 1+ (3.2) ∞ X Cn z n−1 6= 0, n=2 where Cn := n − 1 + 2(1 − α)e−iλ cos λ + (n − 1)ζ an . 2(1 − α)e−iλ cos λ Proof. Letting eiλ p(z) = zf 0 (z) f (z) − α − i(1 − α) sin λ , (1 − α) cos λ we see that p(z) ∈ B and R[p(z)] > 0 It follows from Lemma 1 that 0 zf (z) iλ − α − i(1 − α) sin λ e ζ −1 f (z) 6= (3.3) (1 − α) cos λ ζ +1 (z ∈ U). (z ∈ U; ζ ∈ C; |ζ| = 1). We need not consider Lemma 1 for the case when z = 0, because (3.3) implies that p(0) 6= ζ −1 ζ +1 (ζ ∈ C; |ζ| = 1). It also follows from (3.3) that eiλ [zf 0 (z) − αf (z)] − i(1 − α)f (z) sin λ 6= (1 − α) cos λ (z ∈ U; ζ ∈ C; |ζ| = 1) , J. Inequal. Pure and Appl. Math., 8(4) (2007), Art. 95, 10 pp. ζ −1 ζ +1 f (z) http://jipam.vu.edu.au/ 8 T OSHIO H AYAMI , S HIGEYOSHI OWA , AND H.M. S RIVASTAVA which readily yields (ζ + 1) eiλ [zf 0 (z) − αf (z)] − i(1 − α)f (z) sin λ 6= (ζ − 1)(1 − α)f (z) cos λ (z ∈ U; ζ ∈ C; |ζ| = 1) or, equivalently, (3.4) (ζ + 1)eiλ zf 0 (z) − αeiλ f (z) − ζαeiλ f (z) − i(1 − α)f (z) sin λ − iζ(1 − α)f (z) sin λ 6= ζ(1 − α)f (z) cos λ − (1 − α)f (z) cos λ (z ∈ U; ζ ∈ C; |ζ| = 1) . We find from (3.4) that (ζ + 1)eiλ zf 0 (z) − αeiλ f (z) − ζαeiλ f (z) − ζ(1 − α)eiλ f (z) + (1 − α)e−iλ f (z) 6= 0 (z ∈ U; ζ ∈ C; |ζ| = 1) , that is, that (1 + ζ)eiλ zf 0 (z) + (e−iλ − 2α cos λ − ζeiλ )f (z) 6= 0 (z ∈ U; ζ ∈ C; |ζ| = 1) , which, in light of (1.1) with a0 = a1 − 1 = 0, assumes the following form: ! ! ∞ ∞ X X (ζ + 1)eiλ z + nan z n + (e−iλ − ζeiλ − 2α cos λ) z + an z n 6= 0 n=2 n=2 (z ∈ U; ζ ∈ C; |ζ| = 1) or, equivalently, (3.5) 2(1 − α)z cos λ 1+ ∞ X n + e−2iλ − 2αe−iλ cos λ + (n − 1)ζ 2(1 − α)e−iλ cos λ n=2 ! an z n−1 6= 0 (z ∈ U; ζ ∈ C; |ζ| = 1) . Finally, upon dividing both sides of (3.5) by 2(1 − α)z cos λ 6= 0 and noting that e−2iλ = −1 + 2e−iλ cos λ, we obtain 1+ ∞ X n − 1 + 2(1 − α)e−iλ cos λ + (n − 1)ζ an 6= 0 2(1 − α)e−iλ cos λ π π 0 5 α < 1; − < λ < ; ζ ∈ C; |ζ| = 1 , 2 2 n=2 which completes the proof of Lemma 3 (see also the proof of a known result [1, Theorem 3.1]). By applying Lemma 3, we now prove Theorem 3 below. J. Inequal. Pure and Appl. Math., 8(4) (2007), Art. 95, 10 pp. http://jipam.vu.edu.au/ C OEFFICIENT I NEQUALITIES FOR C ERTAIN C LASSES OF A NALYTIC AND U NIVALENT F UNCTIONS 9 Theorem 3. If f (z) ∈ A satisfies the following condition: " k # ∞ n X X X β γ (−1)k−j [j − α + (1 − α)e−2iλ ] aj k−j n−k n=2 k=1 j=1 " k # ! ∞ X X β γ (3.6) + (−1)k−j (j − 1) aj 5 2(1 − α) cos λ k − j n − k k=1 j=1 π π 0 5 α < 1; − < λ < ; β ∈ R; γ ∈ R , 2 2 then f (z) ∈ SP(λ, α). Proof. Applying the same method as in the proof of Theorem 1, we see that f (z) is in the class SP(λ, α) if n ! ∞ X k X X (3.7) (−1)k−j Cj bk−j cn−k 5 1 n=2 k=1 j=1 where, as before, β γ bn := and cn := , n n the coefficients Cn being given as in Lemma 3. It follows from the inequality (3.7) that 1 |2(1 − α)e−iλ cos λ| " k # ∞ X n X X k−j −iλ · (−1) (j − 1 + 2(1 − α)e cos λ) + ζ(j − 1) aj bk−j cn−k n=2 k=1 j=1 1 2(1 − α) cos λ " k # n ∞ X X X k−j −iλ · (−1) j − α + (1 − α)(−1 + 2e cos λ) b a c k−j j n−k n=2 k=1 j=1 ! " k # n X X + |ζ| (−1)k−j (j − 1)bk−j aj cn−k k=1 j=1 π π (3.8) 51 0 5 α < 1; − < λ < ; ζ ∈ C; |ζ| = 1 , 2 2 which implies that, if f (z) satisfies the hypothesis (3.6) of Theorem 3, then f (z) ∈ SP(λ, α). This completes the proof of Theorem 3. 5 In its special case when β−1=γ =0 β=γ=1 or or β − 2 = γ = 0, Theorem 3 would immediately yield the following corollary. Corollary 7 (cf. [1]). If f (z) ∈ A satisfies any one of the following conditions: (3.9) ∞ X [n − α + (1 − α)e−2iλ ](an − an−1 ) + an−1 + |(n − 1)(an − an−1 ) + an−1 | n=2 5 2(1 − α) cos λ J. Inequal. Pure and Appl. Math., 8(4) (2007), Art. 95, 10 pp. π π 0 5 α < 1; − < λ < 2 2 http://jipam.vu.edu.au/ 10 T OSHIO H AYAMI , S HIGEYOSHI OWA , AND H.M. S RIVASTAVA or (3.10) ∞ X [n − α + (1 − α)e−2iλ ](an − an−2 ) + 2an−2 + |(n − 1)(an − an−2 ) + 2an−2 | n=2 5 2(1 − α) cos λ π π 0 5 α < 1; − < λ < 2 2 or (3.11) ∞ X [n − 1 − α + (1 − α)e−2iλ ](an − 2an−1 + an−2 ) + an − an−2 n=2 + |(n − 2)(an − 2an−1 + an−2 ) + an − an−2 | π π , 5 2(1 − α) cos λ 0 5 α < 1; − < λ < 2 2 then f (z) ∈ SP(λ, α). Remark 4. For λ = 0, Theorem 3 implies Theorem 1. Furthermore, by setting α = 0 in Theorem 3, we arrive at the following sufficient condition for functions f (z) ∈ A to be in the class SP(λ). Corollary 8. If f (z) ∈ A satisfies the following condition: " k # ∞ n X X X β γ (3.12) (−1)k−j (j + e−2iλ ) aj k − j n − k n=2 k=1 j=1 " k # ! ∞ X X β γ + (−1)k−j (j − 1) aj k−j n−k k=1 j=1 π π , 5 2 cos λ 0 5 α < 1; β ∈ R; γ ∈ R; − < λ < 2 2 then f (z) ∈ SP(λ) := SP(λ, 0). R EFERENCES [1] I.R. NEZHMETDINOV AND S. PONNUSAMY, New coefficient conditions for the starlikeness of analytic functions and their applications, Houston J. Math., 31 (2005), 587–604. [2] H. SILVERMAN, E.M. SILVIA AND D. TELAGE, Convolution conditions for convexity, starlikeness and spiral-likeness, Math. Zeitschr., 162 (1978), 125–130. [3] H.M. SRIVASTAVA AND S. OWA (Editors), Current Topics in Analytic Function Theory, World Scientific Publishing Company, Singapore, New Jersey, London and Hong Kong, 1992. J. Inequal. Pure and Appl. Math., 8(4) (2007), Art. 95, 10 pp. http://jipam.vu.edu.au/